Penegakan Hukum Terhadap Pelanggaran Berat Hak Asasi Manusia - Ach. Tahir (UIN Sunan Kalijaga Yogyakarta, 2013)
Gross violation of human rights has always been stalking the world. Wars in Iraq and Palestine not only devastate buildings and infrastructure, but also above all that take the toll of thousands of civilians whose lives are supposed to be protected. United States, all this time claiming as the greatest democracy and champion of human rights, apparently is the one that inflict worst injury to democracy and human rights themselves, as apparent in the fact that until today the issues of wars in Iraq and Palestine are yet to be settled. The United Nations, in its ideal vision the spearhead of justice in global level, is in actuality cowering before the United States and its allies. Sad but true, Law becomes powerless in the face of ambitions of global political power.